Aging with rhythmicity. Is it possible? Physical exercise as a pacemaker - de Souza Teixeira, Alexandre Abilio; Lira, Fábio Santos [UNESP]; Rosa-Neto, José Cesar (Elsevier, 2020)
Aging is associated with gradual decline in numerous physiological processes, including a reduction in metabolic functions and immunological system. The circadian rhythm plays a vital role in health, and prolonged clock disruptions are associated with chronic diseases. The relationships between clock genes, aging, and immunosenescence are not well understood. Inflammation is an immune response triggered in living organisms in response to the danger associated with pathogens and injury. The term ‘inflammaging’ has been used to describe the chronic low-grade-inflammation that develops with advancing age and predicts susceptibility to age-related pathologies. Equilibrium between pro-and anti-inflammatory cytokines is needed for healthy aging and longevity. Sedentary and poor nutrition style life indices a disruption in circadian rhythm promoting an increase in pro-inflammatory factors or leads for chronic low-grade inflammation. Moreover, signals mediated by pro-inflammatory cytokines, such as tumor necrosis factor-alpha and interleukin-6, might accentuate of the muscle loss during aging. Circadian clock is important to maintain the physiological functions, as maintenance of immune system. A strategy for imposes rhythmicity in the physiological systems may be adopted of exercise training routine. The lifelong regular practice of physical exercise decelerates the processes of aging, providing better quality and prolongation of life. Thus, in this review, we will focus on how aging affects circadian rhythms and its relationship to inflammatory processes (inflammaging), as well as the role of physical exercise as a regulator of the circadian rhythm, promoting aging with rhythmicity.
Keywords: Aging; Circadian rhythms; Clock genes; Immunosenescence; Inflammaging